2006
DOI: 10.1118/1.2219091
|View full text |Cite
|
Sign up to set email alerts
|

A realistic phantom for brain-shift simulations

Abstract: Validation of techniques that characterize and correct for brain shift for image guided surgery requires a realistic anthropomorphic phantom for use as a gold standard. The purpose of this study was to determine the characteristics of a deformable brain phantom made of polyvinyl alcohol cryogel (PVAc). The phantom was made of three layers of PVAc with inserted plastic tubes to simulate blood vessels. A catheter with an inflatable balloon was placed under the phantom in order to deform it in a nonlinear manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 8 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…By inflating or deflating the catheter balloon, the phantom would deform in an elastic non-linear manner. A detailed description of the phantom as well as a thorough study of the reproducibility of the deformations can be found in Reinertsen and Collins (2006). The phantom made it possible to test the registration algorithm and segmentation technique as well as the ultrasound imaging setup and the navigation software in a setting with known geometry and simpler deformations than in the human brain.…”
Section: Phantom Study 321 Phantom Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…By inflating or deflating the catheter balloon, the phantom would deform in an elastic non-linear manner. A detailed description of the phantom as well as a thorough study of the reproducibility of the deformations can be found in Reinertsen and Collins (2006). The phantom made it possible to test the registration algorithm and segmentation technique as well as the ultrasound imaging setup and the navigation software in a setting with known geometry and simpler deformations than in the human brain.…”
Section: Phantom Study 321 Phantom Preparationmentioning
confidence: 99%
“…To overcome this problem, parts of the smallest tubes were segmented manually. In the future, a possible solution to this problem would be to fill the tubes with a contrast agent prior to MR imaging Reinertsen and Collins, 2006. Following segmentation, centerlines were extracted using the algorithm described in Section 2.3.…”
Section: Mr Imaging and Vessel Segmentationmentioning
confidence: 99%
“…The creation of a physical model capable of depicting the form of the cerebrum in a realistic manner is not trivial due in part to these deep structures. Previous works in creating brain phantoms have either reduced the depth of the sulci [2], or only recreated the brain's form superficially with dessert gelatin molds [3,4]. Although these phantoms bear a gross cursory resemblance to the human cerebrum, they do not accurately depict its anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the structures being smaller than the image resolution or having insufficient contrast of the markers with respect to the surrounding tissues. For instance, Reinertsen and Collins [4] rely on the presence of bubbles in their phantom to act as landmarks for validation. Our goal is to create a triple modality human brain phantom containing anatomically realistic structures and physically realistic texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation